Redundancy in the World of MAP Kinases: All for One - Saba-El-Leil, Marc K.; Frémin, Christophe; Meloche, Sylvain (Frontiers in Cell and Developmental Biology, 2016)
The protein kinases ERK1 and ERK2 are the effector components of the prototypical ERK1/2 mitogen-activated protein (MAP) kinase pathway. This signaling pathway regulates cell proliferation, differentiation and survival, and is essential for embryonic development and cellular homeostasis. ERK1 and ERK2 homologs share similar biochemical properties but whether they exert specific physiological functions or act redundantly has been a matter of controversy. However, recent studies now provide compelling evidence in support of functionally redundant roles of ERK1 and ERK2 in embryonic development and physiology. In this review, we present a critical assessment of the evidence for the functional specificity or redundancy of MAP kinase isoforms. We focus on the ERK1/ERK2 pathway but also discuss the case of JNK and p38 isoforms.